Undertriage in trauma: Does an organized trauma network capture the major trauma victim? A statewide analysis. Issue 3 (March 2018) - Horst, Michael A.; Jammula, Shreya; Gross, Brian W.; Cook, Alan D.; Bradburn, Eric H.; Altenburg, Juliet; Von Nieda, Danielle; Morgan, Madison; Rogers, Frederick B.
Abstract : BACKGROUND: Proper triage of critically injured trauma patients to accredited trauma centers (TCs) is essential for survival and patient outcomes. We sought to determine the percentage of patients meeting trauma criteria who received care at non-TCs (NTCs) within the statewide trauma system that exists in the state of Pennsylvania. We hypothesized that a substantial proportion of the trauma population would be undertriaged to NTCs with undertriage rates (UTR) decreasing with increasing severity of injury. METHODS: All adult (age ≥15) hospital admissions meeting trauma criteria (ICD-9, 800–959; Injury Severity Score [ISS], > 9 or > 15) from 2003 to 2015 were extracted from the Pennsylvania Health Care Cost Containment Council (PHC4) database, and compared with the corresponding trauma population within the Pennsylvania Trauma Systems Foundation (PTSF) registry. PHC4 contains all hospital admissions within PA while PTSF collects data on all trauma cases managed at designated TCs (Level I-IV). The percentage of patients meeting trauma criteria who are undertriaged to NTCs was determined and Network Analyst Location-Allocation function in ArcGIS Desktop was used to generate geospatial representations of undertriage based on ISSs throughout the state. RESULTS: For ISS > 9, 173, 022 cases were identified from 2003 to 2015 in PTSF, while 255, 263 cases meeting trauma criteria were found in the PHC4 database over the same timeframe suggesting UTR of 32.2%. For ISS > 15, UTR was determined to be 33.6%. Visual geospatial analysis suggests regions with limited access to TCs comprise the highest proportion of undertriaged trauma patients. CONCLUSION: Despite the existence of a statewide trauma framework for over 30 years, approximately, a third of severely injured trauma patients are managed at hospitals outside of the trauma system in PA. Intelligent trauma system design should include an objective process like geospatial mapping rather than the current system which is driven by competitive models of financial and health care system imperatives. LEVEL OF EVIDENCE: Epidemiological study, level III; Therapeutic, level IV.